SEROSURVEILLANCE OF EHRLICHIA RUMINANTIUM ANTIBODIES OF SHEEP USING MAP1-B ELISA IN SENNAR STATE, SUDAN - S. Mohammed, Mohammed; M. Hassan, Shawgi; B. Abdel Rahman, Magdi (Journal of Veterinary Medicine and Animal Production, 2022)
A total of 300 serum samples were collected from adults sheep in Sennar State at five localities namely Sennar, Singa, Dinder, Um Banein and Abu Naama from two farms in each location three times a year, during September 2002 (autumn), January 2003 (winter) and May 2003 (summer). Indirect Enzyme-Linked Immunosorbent Assay (ELISA) was used to determine the sero-prevalence of Ehrlichia ruminantium. The test was performed with recombinant major antigenic protein 1 (MAP1-B). Out of 300 sheep sera tested, 230 (76.6%) were found positive for E. ruminantium antibodies. According to locations, sero- prevalence ranged between 85.1% at Um Banein and 63.3% in Sennar. The E. ruminantium antibodies persisted throughout the year in each location, and seasonality prevalence of the disease showed an increase in sero-prevalence during autumn (80 %) and winter (82 %) while a slight reduction was observed in summer (68 %) but statistically not significant (P < 0.05).